Reconstruction of the Microstructure of Cyanate Ester Resin by Using Prepared Cyanate Ester Resin Nanoparticles and Analysis of the Curing Kinetics Using the Avrami Equation of Phase Change - Hongtao Cao; Beijun Liu; Yiwen Ye; Yunfang Liu; Peng Li (Applied Sciences, 2019)
Bisphenol A dicyanate (BADCy) resin nanoparticles were synthesized by precipitation polymerization and used to modulate the microstructure of the BADCy resin matrix. A microscopic mechanism model was used to characterize the curing process of BADCy resin systems with different contents of the prepared nanoparticles. Due to the curing process of the thermosetting resin being analogous to the crystallization process of the polymer, the Avrami equation was used to analyze the microscopic mechanism of the curing process. The reactive functional groups, structure, and size of the prepared BADCy resin nanoparticles were characterized by FT-IR, SEM, and TEM, respectively. The kinetic parameters of different systems were then obtained using the Avrami equation, and they adequately explained the microscopic mechanism of the curing process. The results showed that the Avrami equation effectively described the formation and growth of gel particles during the curing process of the BADCy resins. The addition of nanoparticles can affect the curing behavior and curing rate. Since the reaction between the BADCy resin nanoparticles and the matrix is dominant, the formation process of the gel particles was neglected. This phenomenon can be understood as the added BADCy resin nanoparticles replacing the formation of gel particles. The reasons for accelerated curing were analyzed from the perspective of thermodynamics and kinetics. Besides this, the Arrhenius equation for non-isothermal conditions correctly accounted for the change in the cross-linked mechanism in the late-stage curing process. A comparison of the theoretical prediction with the experimental data shows that the Avrami theory of phase change can simulate the curing kinetics of different BADCy resin systems well and explain the effects of BADCy resin nanoparticles on the formation of the microstructure.